Radicalism Early Detection and Driving Factors: A Mix Method Study on Islamic University Students in West Java - Muhwan Hariri, Wawan; Lasmi Wardiyah, Mia (CIC Lembaga Riset dan Konsultan Sosial, 2023)
This research is motivated by the issue of religious universities in West Java exposed to radicalism. The purpose of this study was to find indicators of radicalism among students as a measuring tool for potential acts of radicalism among students. The research method used in this research is a qualitative method and a case study with in-depth interviews and participatory radicalism combined with quantitative data to collect data on the magnitude or statistical description of the percentage of students exposed to radicalism. From the results of the research conducted, it was found that the indicators of radicalism can be seen based on the attitude of the tendency to take radical actions based on four things, namely: (1) Intolerance, (2) Fanaticism, (3) Exclusivity, and (4) Revolutionary. The four attitudes show that students with these attitudes are included in the categorization of students who have the potential to act radically. Then the pattern of dissemination can occur through, (1) the spread of radicalism by means of direct meetings. This distribution is done through closed recitations with a limited number of participants. With the aim of conveying doctrine and preventing rejection (refutation) from other people who have wider religious knowledge and can reject the arguments of the proponent of doctrine. (2) Using technology by uploading videos and photos of their activities to invite movements they believe to be the most correct actions. (3) By doing propaganda through the news media which is spread through the telegram. This research has an impact on early detection of attitudes and characteristics of students who have the potential to carry out radical attitudes and actions. Then this research has an impact on strengthening and anticipating the possibility of radical actions in Islamic Religious Colleges in West Java.